REDUCING ANXIETY IN SPEAKING ENGLISH THROUGH PAIR WORK - Dalisa, Yuniarti; ., Apriliaswati; ., Husin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aimed to reduce anxiety in speaking English through pair work of Students of class eight B in the second academic year 2013/2014 of SMP N 11 Pontianak. The writer applied Classroom Action Research which consisted of three cycles. The subject of this research was the second year students of class eight B of SMP N 11 Pontianak in Academic Year 2013/ 2014. They consisted of 38 students. The data was collected using observation checklist, questionnaire, performance test, and field notes. Pair Work reduced students anxiety in speaking English in each cycle were 46%, 61.1%, and 78.4%. Pair work encouraged students to be confidence in speaking English in each cycle were 46%, 63.8%, and 78.4%. Pair Work encouraged students to speak up by pair dialogue card, pair blank dialogue card, and pair role play. In conclusion, pair work helped the teacher to reduce her students’ anxiety in speaking English. Keywords: Anxiety, Pair Work Abstrak: Penelitian ini bertujuan untuk mengurangi kecemasan berbicara dalam bahasa Inggris melalui Pair work pada siswa kelas VIII B pada semester genap tahun ajaran 2013/2014 di SMP N 11 Pontianak. Penulis menerapkan Penelitian Tindakan kelas dalam tiga siklus. Subjek penelitian ini adalah siswa kelas VIII B di SMP N 11 Pontianak tahun ajaran 2013/2014, yang terdiri dari 38 siswa. Data dikumpulkan menggunakan observasi ceklist, angket, tes tampil didepan kelas, dan catatan lapangan. Pair work mengurangi kecemasan siswa dalam berbicara Bahasa Inggris pada setiap siklus adalah 46%, 61.1%, and 78.4%. Pair work mendorong siswa menjadi percaya diri dalam berbicara bahasa Inggris pada setiap siklus adalah 46%, 63%, dan 78.4%. Pair work mendorong siswa untuk berbicara melalui pair dialogue card, pair blank dialogue card, dan pair role play. Kesimpulannya, pair work membantu guru mengurangi kecemasan siswa dalam berbicara bahasa Inggris Kata kunci: Kecemasan, Pair work